2018
DOI: 10.1002/cne.24606
|View full text |Cite
|
Sign up to set email alerts
|

Primate neocortex development and evolution: Conserved versus evolved folding

Abstract: The neocortex, the seat of higher cognitive functions, exhibits a key feature across mammalian species—a highly variable degree of folding. Within the neocortex, two distinct subtypes of cortical areas can be distinguished, the isocortex and the proisocortex. Here, we have compared specific spatiotemporal aspects of folding between the proisocortex and the isocortex in 13 primates, including human, chimpanzee, and various Old World and New World monkeys. We find that folding at the boundaries of the dorsal iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 55 publications
(133 reference statements)
1
13
0
Order By: Relevance
“…Although smaller mammals tend to have less folded neocortices, with the GI close to 1.0, the relationship between overall brain size and folding is not universal, with examples of large mammals such as the manatee having a lissencephalic cortex (Welker, 1990;Pillay and Manger, 2007;Lewitus et al, 2014;Vaid et al, 2018). Similarly, phylogenetic lineage relationships are also not determinative of cortex folding as exemplified by marmosets, which are lissencephalic, in contrast to most other primates, which possess gyrencephalic neocortices (Zilles et al, 1989;Kelava et al, 2012;Lewitus et al, 2014;Mitchell and Leopold, 2015;Vaid et al, 2018;Namba et al, 2019). Humans, next to cetaceans and elephants, are among the species with the highest GI (Zilles et al, 1988(Zilles et al, , 1989Kelava et al, 2012;Lewitus et al, 2014;Namba et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Although smaller mammals tend to have less folded neocortices, with the GI close to 1.0, the relationship between overall brain size and folding is not universal, with examples of large mammals such as the manatee having a lissencephalic cortex (Welker, 1990;Pillay and Manger, 2007;Lewitus et al, 2014;Vaid et al, 2018). Similarly, phylogenetic lineage relationships are also not determinative of cortex folding as exemplified by marmosets, which are lissencephalic, in contrast to most other primates, which possess gyrencephalic neocortices (Zilles et al, 1989;Kelava et al, 2012;Lewitus et al, 2014;Mitchell and Leopold, 2015;Vaid et al, 2018;Namba et al, 2019). Humans, next to cetaceans and elephants, are among the species with the highest GI (Zilles et al, 1988(Zilles et al, , 1989Kelava et al, 2012;Lewitus et al, 2014;Namba et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Many “higher order” behaviors displayed by mammals, including primates, and humans specifically, have been proposed to be supported by uniquely evolved neurodevelopmental programs executed during forebrain development in these lineages (Kriegstein et al, 2006; Namba & Huttner, 2017; Namba, Vaid, & Huttner, 2019; Nowakowski, Pollen, Sandoval‐Espinosa, & Kriegstein, 2016). This suggestion is intuitively appealing for humans, particularly when trying to frame knowledge about complex psychological processes (including multisensory, cognitive, and emotional processes) associated with human brain function and human behavior.…”
Section: A Focus On the Forebrainmentioning
confidence: 99%
“…However, although ferrets are a superior model organism in this regard, they present several limitations, as follows. First, although the ferret brain is bigger than that of mouse and gyrified, it does not exhibit a prominent temporal lobe and lateral fissure (Hutchinson et al, 2017), two specific macroscopic features found in primate brains (Bryant and Preuss, 2018; Namba et al, 2019). Second, the available ferrets are outbred animals, and hence their genetic background is not homogeneous, in contrast to that of the inbred mouse lines.…”
Section: Experimental Models For Studying Human Neocortical Malformatmentioning
confidence: 99%